Metabolic reservoir cycles in cancer. (November 2022) - Zhang, Cissy; Quinones, Addison; Le, Anne
Abstract: Cancer cells possess various biological processes to ensure survival and proliferation even under unfavorable conditions such as hypoxia, nutrient deprivation, and oxidative stress. One of the defining hallmarks of cancer cells is their ability to reprogram their metabolism to suit their needs. Building on over a decade of research in the field of cancer metabolism, numerous unique metabolic capabilities are still being discovered in the present day. One recent discovery in the field of cancer metabolism that was hitherto unexpected is the ability of cancer cells to store vital metabolites in forms that can be readily converted to glucose and glutamine for later use. We called these forms "metabolic reservoirs." While many studies have been conducted on storage molecules such as glycogen, triglyceride, and phosphocreatine (PCr), few have explored the concept of "metabolic reservoirs" for cancer as a whole. In this review, we will provide an overview of this concept, the previously known reservoirs including glycogen, triglyceride, and PCr, and the new discoveries made including the newly discovered reservoirs such as N-acetyl-aspartyl-glutamate (NAAG), lactate, and γ- aminobutyric acid (GABA). We will also discuss whether disrupting these reservoir cycles may be a new avenue for cancer treatment. Highlights: Cancer cells utilize "metabolic reservoirs" to store crucial energy-producing molecules as other substrates for later use. Metabolism of well-known storage molecules such as glycogen, triglycerides, and PCr, are reprogrammed in cancer. Cancer cells have developed unique reservoirs including NAAG, lactate, and GABA. Cancer cells are able to utilize molecules in the extracellular space as a source for essential building blocks. Disrupting "metabolic reservoirs" may help improve current cancer treatment.